The Possession Law Suit, Caused by Forbidden Immissions - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
In the Serbian Law and in most of jurisdictions, there are limits on exercising the right of property. The real estate owner must refrain from activities by which the use of other real estate is being impoded through the immission of execive gasses, vapors, smoke, heat noise, tremors etc. The property ownership whose is affected by immission exceeding the set limits, has the right to request a stop ef immisions which exceeded the allowed volume of immissions. In artcle autor describes various kinds of immissions. The general feature of this law suit is that there is only discussion on the facts and not for a legal matters. Subject matter jurisdictionfor the resolution of such disputes belongs to the court of general jurisdiction, while the disputes itself is a litigation. The special rule of procesedings of action of disturbance are: provisionality of the protection of possession; urgency in procedings; initiation of proceedings; limiting of objection; prescribing temporary measures; rendering a ruling in the form of order; appeals which may be filed within a short deadline and which does not have suspensive effect (do not delay the execution of the order; revision is not allowed etc.